Preferred Information Sources by Shrimp Farmers in Maharashtra, India - Sandesh V. Patil; Arpita Sharma (Journal of Indian Fisheries Association, 2022)
An investigation was carried out to study the preferred information sources by the shrimp farmers in Maharashtra. Data was collected from 151 shrimp farmers from four coastal districts (viz., Palghar-Thane, Raigad, Ratnagiri and Sindhudurg) in Maharashtra. A pretested interview schedule was used to collect information from shrimp farmers. Three-point continuum scale was used to know the preferred sources of information by shrimp farmers and Weighted Average (WA) technique was used to analyse and rank various information sources preferred by shrimp farmers. The findings revealed that aqua company technicians/ input dealers (WA- 88.67) followed by use of internet/social media (WA- 85.67) were the preferred sources of information. Fisheries institutions/organizations like college of fisheries, Ratnagiri (WA- 73.00)and ICARCentral Institute of Fisheries Education as well as Marine Product Export Development Authority (WA- 72.33) were the third and fourth preferred source of information. Shrimp farmers were relatively better educated and maximum used mobile phones, therefore, internet / social media-based information exchange can be used as a viable strategy to provide information and services. It would be better if private sector, ICT and Government organisations complement each other through convergence.